EXPLORACIÓN DE LAS EMOCIONES AUTOPERCIBIDAS FRENTE AL ETIQUETADO FRONTAL Y SU RELACIÓN CON LA DECISIÓN DE COMPRA. - Eugenia Chulibert, María; Labory, Johana Pees; Kalfaian, Laura; Gamberale, Cristina; Katz, Mónica; Priore, Mariana; Teresa Panzitta, María (Actualización en Nutrición)
Introduction: Argentina is facing a significant increase in non-communicable chronic diseases, with an overweight prevalence of 66.1% and a rise in diabetes from 9.8% in 2013 to 12.7% in 2018. To address these issues, in October 2021, Law No. 27,642 for the Promotion of Healthy Eating was enacted, introducing front-of-package labeling (FoPL) to inform consumers about products containing excessive amounts of critical nutrients. Materials and Methods: A cross-sectional descriptive study was conducted using an online self-administered questionnaire. The questionnaire assessed sociodemographic variables (gender, age, education level), responsibility for household food purchases, knowledge and perception of FoPL, self-perceived emotions in response to FoPL, and their influence on purchase decisions. Results: A total of 262 participants (88% female) completed the survey. Seventy-two percent understood the warning labels on food items, and 54% felt influenced by them during purchases; however, 92% continued to buy products bearing these labels. The predominant self-perceived emotions towards the labels were indifference (36%) and security (19%). The emotion experienced was significantly associated with the purchase decision (p<0.01), indicating that negative emotions such as aversion, anxiety, and distress decreased the likelihood of purchase, while indifference increased it. Conclusions: These findings suggest that while consumers comprehend and consider warning labels, emotional responses play a crucial role in the effectiveness of FoPL in altering dietary behaviors. Therefore, these emotional factors should be taken into account when evaluating and designing such labeling systems.